Deported to death : how drug violence is changing migration on the US-Mexico border - Slack, Jeremy (California series in public anthropology, 2019)
"Deported to Death explores the consequences of the United States' policies of mass removal into some of the most dangerous regions in the world. Over the past decade Mexico has experienced an earthshaking conflict over control of drug trafficking while millions of people were simultaneous deported directly into the midst of this violence often without identification, money, contacts or in the middle of the night. This book explores how the violence associated with the drug trade has impacted the movement of people back and forth across the border. This includes Central Americans and Mexicans, travelling north, but also those that have been removed. By studying the dynamics of removal and the ways that deportees are targeted by organized crime along Mexico's northern border, not only does it give us a better sense of the consequences of a militarized war on drugs, but it helps us understand the violence intrinsic to forced removal. The dynamics of border enforcement make it easy to kidnap, extort and kill deportees who are neither from the border, nor are they at their final destination. This puts people at extreme risks that we are woefully ill equipped to address"--Provided by publisher